Longitudinal benefits of pre-departure pragmatics instruction for study abroad: Chinese as a second/foreign language. (2nd February 2019) - Wang, Jiayi; Halenko, Nicola
Abstract : Whilst the study of second language pragmatic development in study abroad (SA) contexts has gained momentum in recent years, research on L2 Chinese pragmatics, in general, remains in its infancy and is therefore limited. Longitudinal studies on the effects of instruction before, during and after SA remain scant. Following a short pre-SA pragmatics intervention on formulaic expressions with a group of UK undergraduate learners of Chinese, qualitative data in three phases (before, during, and after a year abroad in China) were collected and analysed to shed light on the perceived benefits of the treatment. The findings show that in all three phases, learners highly valued the instruction provided, but they seemed to benefit from the sociopragmatic input the most, particularly in the pre-departure stage and after completion of the SA period. The findings will be discussed in relation to the learners' accounts of their SA experiences and the implications for pre-SA instruction.